Enhancing the Naturalness Through Cultural Adaptation in Translating English-Indonesian Advertisements - Jepri, Jepri - (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
ABSTRACT Cultural adaptation plays an important role in the process of translating ads, whereby Hofstede’s theory of cultural dimension holds true for the case of English-Indonesian translation as well (Hofstede, 1980: p. 60). Marketing strategies must incorporate cultural elements, dialects, and images that resonate with the community. This is a case study to establish whether and to what extent cultural adaptation increases the credibility of English and Indonesian advertisement translations as well as interest and involvement of the audience. Focus was also placed on cultural theories of moderation and localization, including Hofstede’s model of cultural parameters (Hofstede, 1980; De Mooij, 2011), The study highlights the need for being culturally sensitive while translating advertisements. While adaptation increases the naturalness and appeal, it raises questions on how to balance fidelity to the original with accuracy of linguistics and cultural nuances. Keywords: cultural adaptation, Advertising Translation